EVALUATION OF GENETIC DIVERSITY OF RALSTONIA SOLANACEARUM STRAINS USING RAPD-PCR - Р. В. Грицай; Л. Д. Варбанець; О. С. Броварська; Н. В. Житкевич; Т. М. Олійник (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2011)
There were analysed 9 strains of Ralstonia solanacearum, obtained from New Zealand collection and collection of the Department of phytopathogenic bacteria of D.K. Zabolotny Institute of Microbiology and Virology on the basis of RAPD-PCR. According to the obtained results high level of genetic diversity was established and phylogenic tree was constructed. The distribution of the strains into genetic clusters shown similarity between the strains of biovar 1. No association was found between amplified sequences and determination of lipopolysaccharide chemotypes.